1992
DOI: 10.1111/j.1439-0450.1992.tb01155.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Campylobacter Carriage Rates in Diarrheic and Healthy Pet Animals

Abstract: Summary To explore the clinical significance of campylobacter infections for dogs and cats we compared intestinal carriage rates for Campylobacter sp. between animals with gastroenteritis and healthy controls. We cultured fecal specimens of 405 diarrheic dogs and 203 cats as well as 71 asymptomatic dogs and 35 cats using a selective medium in addition to filtration on a non‐selective blood agar plate. We identified 224 campylobacter isolates using conventional phenotypic tests and DNA hybridization. There were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
61
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(72 citation statements)
references
References 11 publications
9
61
2
Order By: Relevance
“…Furthermore, we found that isolation of C. jejuni was correlated with the age of the dogs, as the majority of C. jejuni strains were found in dogs under 1 year of age. Similar findings have been published in other studies of healthy dogs by Burnens et al (5) and by Moser et al (27). In humans, Lastovica and Engel (20) also found that C. jejuni predominated in children younger than a year, whereas C. upsaliensis was more common in older children.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, we found that isolation of C. jejuni was correlated with the age of the dogs, as the majority of C. jejuni strains were found in dogs under 1 year of age. Similar findings have been published in other studies of healthy dogs by Burnens et al (5) and by Moser et al (27). In humans, Lastovica and Engel (20) also found that C. jejuni predominated in children younger than a year, whereas C. upsaliensis was more common in older children.…”
Section: Discussionsupporting
confidence: 78%
“…Certainly, Campylobacter carriage in healthy pet dogs is common according to several studies in the last two decades, with reported carrier rates from 21 to 75% (4,5,12,16,27,29,35,40,42). The species distribution of isolates from dogs differs considerably between publications and years.…”
mentioning
confidence: 99%
“…Like other investigators, we found a high carriage rate for asymptomatic dogs (61), and in accordance with many others, there was no significant difference in isolation rates between healthy and diarrheic dogs (48,66,73,77). In contrast, Fleming (21) and Nair et al (59) found a higher prevalence in diarrheic dogs, and Burnens et al noted that this relationship only held true for younger dogs (9).…”
Section: Discussionmentioning
confidence: 40%
“…The species identified among our feline isolates were expected, as cats are established reservoirs of C. jejuni, C. upsaliensis, and C. helveticus (5,9,23,24,29). Such a high frequency of infection with C. helveticus (50%), however, could not be found in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal carriage rates for Campylobacter spp. between dogs with gastroenteritis and healthy controls were compared [31]. For dogs older than 12 months, there was no difference in Campylobacter carriage rates between diarrheic and healthy animals.…”
Section: Discussionmentioning
confidence: 99%